Using Yeast Extract as an Approach to Increase Flavonolignans Content in Cell Suspension Culture of Milk Thistle Plant Via Elicitation Mechanism - S Rahimi Ashtiani; T Hasanloo; R Bihamta Mohammad (Institue of Medicinal Plants, ACECR, 2009)
Background: Silybum marianum (L.) Gaertn is a kind of medicinal plants. Silymarin is a derivate substance from the fruits of Milk Thistle plant which is consists of a large number of flavonolignans. Cell cultures derived from this species could be an alternative for production of flavonolignans. Elicitors cause enhancement in metabolite production by effecting on key enzymes in secondary metabolites pathways. In this study various level of Yeast extract in 5 different exposure time have been used as an biotic elicitor in order to evaluation the effect of Yeast extract on silymarin production and cell growth and nomination the best time and best consistence of the elicitor. Objective: In this study various level of Yeast extract in 5 different exposure time have been used as an biotic elicitor in order to evaluation the effect of Yeast extract on silymarin production and cell growth and nomination the best time and best consistence of the elicitor. Methods: In this work after preparation cell suspension culture of S. marianum, the effects of various level of Yeast extract (1, 2. 4, 6 and 8 mg/50 ml culture) in 6 different exposure time (12, 24, 48, 72, 144 and 216 h) on flavonolignans production by High Performance Liquid Chromatography (HPLC) have been studied. Results: Determination and quantification of flavonolignans showed that cell suspension cultures of S. marianum were consists of a large number of flavonolignans including silychristin, silydianin, silybin, isosilybin and taxifolin. The results showed that Yeast extract cause improvement in silymarin content in the media treated with 6 (mg / 50 ml culture) Yeast extract at the end of 72h which was 5- fold to compare the control and the maximum cell Dry weight was 5.82 g in the media treated with 4 mg/ 50 ml culture Yeast extract at the end of 24h. Conclusion: In this experiment it has been observed that cell suspension culture of S. marianum are susceptible to elicitation by Yeast extract and it can be extremely useful in increasing productivities in cell suspension culture of Milk thistle plant.